Ptilocephala muscella (Denis & Schiffermüller, 1775) prvič najdena v Sloveniji (Lepidoptera: Psychidae) - Predovnik, Željko (Acta entomologica slovenica (Ljubljana), 2009)
The inventory of Slovene bagworms has now been enlarged by one species. The contribution deals with the find of the species Ptilocephala muscella (Psychidae), which was observed in Križevci, in Goričko Landscape Park (Northeast Slovenia). The find is not surprising, since P. muscella is presentin all neighbouring countries with the exception of Croatia.
Keywords: entomologija; metulji; najdbe; Slovenia; Slovenija